PENGARUH HUMBLE LEADERSHIP TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR: MEKANISME KEPERCAYAAN KEPADA PEMIMPIN - Indra Agus Setiadi; M. Rasyid Abdillah; Fathurahman, Fathurahman (Indragiri Research Center (ingreat), 2025)
This research is also motivated by a research gap in previous studies, where many discuss leadership styles broadly, but there is still minimal research in Indonesian that explores the relationship between humble leadership and OCB, with trust in leaders as a mediating variable. The research is a type of quantitative descriptive research with a causal research design with a population of state civil servants at the Siak Regency DPRD Secretariat with a population of 150 people and a sample using the census method. Data collection techniques using questionnaires and distribution using google forms. The data analysis tool in this study is Structural Equation Modeling (SEM) processed using SmartPLS 32.9 for data processing. From the findings of this study, it was found that humble leadership has a positive and insignificant effect on organizational citizenship behavior (hypothesis 1 is rejected), humble leadership has a positive and significant effect on trust in leaders (hypothesis 2 is accepted), trust in leaders is positive and significant on organizational citizenship behavior (hypothesis 3 is accepted) and humble leadership has a positive and significant effect on organizational citizenship behavior through trust in leaders (hypothesis 4 is accepted).